Best articles rewarded - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Association for the Development of Education in Africa (ADEA) has launched an award scheme for the best article on education to appear in the African press. A paid study visit in Europe and prizes of 2,000 and 1,000 will be granted to the...